Pregnant women in the street context: social vulnerability - Natally Araújo Pereira dos Santos; Sidney Bruno Lima da Silva; Ana Beatriz Oliveira da Mota; Matheus Henrique Estevam; Erika Simone Galvão Pinto; Nilba Lima de Souza (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to identify elements that influence and contribute to the social vulnerability experienced by women who gave birth on the streets, according to their perceptions. Method: a qualitative study using Thematic Oral History, developed in a shelter for homeless women. The population included mothers who gave birth on the streets. The interviews were processed in three phases, as recommended by Meihy and Ribeiro: transcription, textualization, and transcreation. The data were analyzed in light of the theory of thematic analysis proposed by Braun and Clarke. Results: the following thematic axes emerged from the interviewees’ discourses: Thematic Axis 1: Drug addiction as an escape from the reality they live in; Thematic Axis 2: Immersed in violence; Thematic Axis 3: The lack of health care; Thematic Axis 4: The rupture of family ties; Thematic Axis 5: Invisibility to society. Conclusion: women who experience pregnancies in the context of the streets are immersed in conditions that generate and/or enhance social vulnerability, which permeates the specific needs of the gestation process, the obstacles inherent to living on the streets, as well as the deprivation of rights.